NEGOTIATING LINGUISTIC IDENTITY AND BELONGING IN EUROPE (= Nationalisms across the Globe 14). Eds. Virve-Anneli Vihman and Kristiina Praakli - Krzysztof E. Borowski; Alexandra Fisher (Slavia Centralis, 2020)
The article presents the 14th volume of the Nationalisms across the Globe series – Negotiating Linguistic Identity: Language and Belonging in Europe.